Hierarchical trait filtering at different spatial scales determines beetle assemblages in deadwood. (2nd October 2022) - Neff, Felix; Hagge, Jonas; Achury, Rafael; Ambarlı, Didem; Ammer, Christian; Schall, Peter; Seibold, Sebastian; Staab, Michael; Weisser, Wolfgang W.; Gossner, Martin M.
Abstract: Environmental filters—including those resulting from biotic interactions—play a crucial role during the assembly of ecological communities. The importance of scale has thereby been acknowledged but filters at different scales have rarely been quantified in relation to each other, although these hierarchically nested filters eventually determine which communities assemble from a regional species pool. Saproxylic beetles offer an ideal system to study such hierarchically nested environmental filters. Three steps of filtering during the community assembly of these deadwood‐dependent beetles are proposed. First, starting from a regional species pool, species must disperse to forest sites. Second, within a site, individuals need to find a patch with preferred microclimatic conditions. Third, the conditions of a single deadwood object (i.e. tree species identity, decomposition stage) at this patch will determine, which species colonise and establish. To study these hierarchical filters, we used unique long‐term data ets of saproxylic beetle diversity from trap catches at 29 sites and from emergence traps on 694 experimentally installed deadwood logs at the same sites in three regions in Germany. To relate different environmental filters to beetle assemblages, we used a set of 13 functional traits that are hypothesised to relate to different filters at different scales. We show that all three hierarchical filtering steps resulted in reductions of functional diversity and simultaneous shifts in the functional composition of beetle assemblages, reflecting the roles of different traits in response to different filters. Trait composition changed most strongly at the last filtering step, that is, depended on tree species identity and decomposition stage. We showed that if community assembly is analysed as a hierarchical multi‐step process based on data from different spatial scales, environmental filters can be quantified at these scales. As such, a better understanding of the role that different filters play at different spatial scales can be reached. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Zusammenfassung: Umweltfilter—einschliesslich solcher, die sich aus biotischen Wechselwirkungen ergeben—bestimmen massgeblich, wie sich lokale ökologischen Gemeinschaften aus einem Pool regional verfügbarer Arten zusammensetzen. Dabei spielen hierarchisch verschachtelte Filter auf verschiedenen räumlichen Ebenen eine Rolle. Diese wurden selten in Relation zueinander quantifiziert. Totholzkäfer sind sehr gut geeignet, um solche hierarchisch verschachtelten Umweltfilter zu untersuchen. Hier schlagen wir drei räumliche Ebenen vor, auf denen Umweltfilter die Zusammensetzung von Totholzkäfergemeinschaften beeinflussen. Erstens müssen die Arten, ausgehend von einem regionalen Artenpool, geeignete Waldstandorten erreichen. Zweitens müssen die Arten innerhalb eines Standorts ein Habitat mit den bevorzugten mikroklimatischen Bedingungen finden. Drittens bestimmen die Charakteristika eines einzelnen Totholzobjekts (d.h. Baumart, Zersetzungsstadium) innerhalb des Habitats, welche Arten sich ansiedeln und etablieren. Um die hierarchischen Filter zu untersuchen, nutzten wir einzigartige Langzeitdatensätze zu Totholzkäfergemeinschaften aus Fallenfängen an 29 Standorten und aus Emergenzfallen an 694 experimentell ausgebrachten Totholzstämmen an denselben Standorten in drei Regionen in Deutschland. Um die verschiedenen Umweltfilter mit den Käfergemeinschaften in Beziehung zu setzen, verwendeten wir 13 funktionelle Merkmale, von denen erwartet wird, dass sie mit verschiedenen Filtern auf verschiedenen Ebenen in Verbindung stehen. Wir zeigen, dass Filter auf allen drei räumlichen Ebenen zu einer Verringerung der funktionellen Vielfalt und gleichzeitig zu Verschiebungen in der funktionellen Zusammensetzung von Käfergemeinschaften führten. Die funktionelle Zusammensetzung änderte sich am stärksten auf der letzten räumlichen Ebene, d.h. sie war stark abhängig von der Baumart und dem Zersetzungsstadium. Indem wir in einem hierarchischen, mehrstufigen Prozess analysieren, wie sich Gemeinschaften zusammensetzen, zeigen wir, dass Umweltfilter auf verschiedenen räumlichen Ebenen die Totholzkäfergemeinschaften prägen. So können wir die Rolle, welche verschiedene Filter auf verschiedenen räumlichen Ebenen spielen, besser verstehen.